Factors Influencing Utilization of Chronic Disease Management Programs among Adults with Diabetes in Primary Care: A Scoping Review - Shofiyana Shofiyana; Sutopo Patria Jati; Farid Agushybana (Universitas Pahlawan Tuanku Tambusai, 2026)
Chronic disease management programs (CDMPs) in primary health care aim to improve outcomes and reduce avoidable utilization for people with type 2 diabetes, yet enrollment, engagement, and sustained use vary widely across settings. Objective: To map factors influencing utilization of CDMPs among adults with diabetes in primary care and identify leverage points to improve uptake and sustained participation. Methods: We conducted a scoping review of 12 original studies across diverse health systems, synthesizing patient-, program-, provider-, system-, and technology-level determinants of utilization. Results: Utilization was shaped by insura nce coverage and costs, care access and convenience, service quality, referral processes, provider capacity, health literacy, motivation, social support, and fit with clinic workflows. Evidence from Indonesia’s Prolanis linked program engagement to national insurance membership, primary care use, and glycemic monitoring, with active participation associated with fewer outpatient visits (Putra et al., 2024). Family support and perceived service quality strongly predicted active participation (Cahyaningrum et al., 2024). Technology-enabled programs such as remote patient monitoring (RPM) and telemedicine showed promise for widening access when adequately resourced and integrated, but sites reported variable delivery strategies and implementation barriers (staffing, leadership buy-in, reimbursement, and EHR workflows) (Kirkland et al., 2023). Conclusions: Multi-level, context-adapted strategies are needed to optimize CDMP utilization, including streamlined EHR-enabled referrals, aligned incentives, family-engaged care, provider training, and flexible digital options that fit clinic workflows and patient preferences.